Experimentally reduced nest-building costs result in higher provisioning rates but not increased offspring fitness in Blue Tits. (1st March 2016) - Mainwaring, Mark; Hartley, Ian
The energetic costs associated with nest construction are becoming increasingly apparent, yet we still know remarkably little about how those costs affect parental care during the subsequent egg laying, incubation, nestling provisioning and fledgling stages of reproduction. Here we describe a study where we provided experimental pairs of Blue Tits (Cyanistes caeruleus) with supplementary food throughout the nest-building period and then quantified nest characteristics, incubation behaviours and nestling provisioning rates at experimentally fed and unfed control nests. We have already reported that experimental females built heavier nests than unfed females and here we extend that study by showing that whilst hatching asynchrony and brood sizes at hatching did not differ between treatments, males at experimental nests provisioned their offspring at significantly higher rates than did males at control nests. As female provisioning rates did not differ significantly between treatments, total parental provisioning rates were higher at experimental nests, although brood sizes and the mass of nestlings at pre-fledging did not differ between treatments. This implies that when the energetic costs of nest construction were indirectly reduced via the provision of supplementary food, females responded by constructing larger nests. Females did not alter their incubation or provisioning behaviours but males did increase their provisioning rates. Unfortunately, our experimental design means that we are unable to disentangle the relative contributions of the provision of supplementary food and the size of the female-built nest in causing male provisioning rates to be higher at experimental nests. In summary, our study suggests that the energetic costs of nest construction are carried over into future stages of reproduction in a sex-specific and complex manner.